Sustainable Development Goal in the beekeeping sector and its cooperative network - Andrieu, Jimena (2023)
The Sustainable Development Goals (SDGs) are a global priority in terms of com mitment to the responsible development of society. This paper focuses on beekeeping as a strategic sector of the Argentine economy due to its important socio-economic and environmental impacts. The objective of this research is to analyze the practices of beekeeping entities in their alignment with the achievement of the SDGs (with a focus on SDGs 5, 8, 9, 12 and 17), paying special attention to the differential contribution of companies with cooperative formula. It focuses on actions related to work organization, production, innovation and market insertion. To this end, we used variable significance analysis for 2x2 matrices and multivariate factor analysis of multiple correspondences. The results obtained show that there is a positive alignment between the practices of beekeeping sector entities and SDG 5, SDG 12 and SDG 17, with a differential and positive trend for organizations with a cooperative formula. However, the results also show the future challenges faced by the sector, especially with regard to SDGs 8 and 9.